2023
DOI: 10.1021/acsapm.3c00481
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Thermogalvanic Gel for Simultaneous Waste Heat Recovery and Thermal Management of Electronics

Abstract: Due to their distinctive characteristics of adequate flexibility, stability, and functional diversity, thermogalvanic gels have demonstrated tremendous promise in the area of renewable energy sources. However, their inability to adapt to low or high temperature environments greatly limits their practical applications. In this work, an anhydrous thermogalvanic gel prepared from dimethyl sulfoxide (DMSO)/ethylene glycol (EG) binary organic solvent is developed with Fe 3+/2+ as a redox pair, which displays an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Moreover, we compared the stress–strain data of LM–VGA/BPDMS with other previously reported materials in Fig. 2h, 5,15,18,39–50 further highlighting the soft elasticity of our composites. Overall, the exceptional flexibility and ultra-low elastic modulus of the material not only allow it to conform to interfaces with complex surface structures but also ensure thorough gap filling on the contact surface under low installation pressure conditions.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, we compared the stress–strain data of LM–VGA/BPDMS with other previously reported materials in Fig. 2h, 5,15,18,39–50 further highlighting the soft elasticity of our composites. Overall, the exceptional flexibility and ultra-low elastic modulus of the material not only allow it to conform to interfaces with complex surface structures but also ensure thorough gap filling on the contact surface under low installation pressure conditions.…”
Section: Resultsmentioning
confidence: 54%
“…4h presents statistical data representing the relationship between the thermal conductivity and elastic modulus of silicone, foams, ceramics, and various polymeric composites enhanced with fillers such as LM, carbon nanotubes, and graphene, among others. 15,19,27,34,37,45,50,59–63 The composite material thus developed, featuring low modulus, high deformability, and high κ , demonstrates pressure-controlled heat dissipation capabilities and dynamic thermal dissipation in complex environments. This surpasses the heat dissipation performance of commercial TIMs, highlighting its potential as a high-performance TIMs for flexible electronics.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the combination of dimethyl sulfoxide (DMSO) and PVA has recently garnered attention. In this direction, Zhang et al [94] capitalized on this combination to develop a thermogalvanic gel. As shown in Figure 6e, the presence of DMSO greatly enhanced the tensile strength of the gel at the expense of reduced tensile strain.…”
Section: Impacts Of Hydrogel Compositionmentioning
confidence: 99%
“…In previous studies, Hu et al have demonstrated the viability of thermoelectric hydrogels as thermal recovery generators . Zhang et al have focused on the sensing capabilities of thermoelectric couple hydrogels and have proven their wide range of applications in medical and daily life, offering new directions for smart living. Additionally, Ma et al have successfully utilized thermoelectric hydrogels for thermal management, providing assistance in monitoring and protecting various heat-generating electronic devices. Furthermore, in the research conducted by Sun et al, significant breakthroughs have been made in the use of ion thermoelectric hydrogels relying on the Seebeck effect, showcasing the remarkable efficiency of thermoelectric hydrogels. , These quasi-solid-state thermoelectric coupler hydrogel electrolytes, through the manipulation of electrodes and electrolytes, have shown a certain level of efficiency in recovering thermal energy. , The primary research focus should be on the cost-effectiveness of preparing thermoelectric hydrogels and their subsequent thermal energy absorption efficiency, as these are vital factors in the development of functional products for thermal energy recovery. An increase in heat absorption at the hot end of thermoelectric coupler hydrogels results in a greater temperature difference between the hot and cold ends, leading to enhanced power output .…”
Section: Introductionmentioning
confidence: 99%